Proceedings of the 1st International Conference on Science, Health, Economics, Education and Technology (ICoSHEET 2019) 2020
DOI: 10.2991/ahsr.k.200723.045
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Level of Knowledge and Attitude of Aged Women About Early Detection of Cancer Leaf Cancer With Behavior of Examination of Acetic Acid Inspection

Abstract: According to an evaluation in early 2016 the coverage of IVA exams in Bogor City was still very low at around 10.4%. This is far from the target of the Bogor City Health Office, which in 85 years is 85% or an annual target of 20% of the population at risk. The purpose of this study was to determine the relationship of the level of knowledge and attitudes of women of childbearing age about early detection of cervical cancer with an examination of Visual Acetic Acid Inspection behavior in the working area of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
0
0
Order By: Relevance
“…The results in this study were similar to research conducted in Bogor, which showed that education level directly influenced perceptions of VIA examinations and other cervical cancer examinations. 21 This was also shown in previous studies which showed that the level of education related to the level of knowledge about cervical cancer, examinations in the framework of early detection of cervical cancer, the dangers posed, and examination methods. 12,21,22 Based on the analysis conducted, it is known that in general the poor level of acceptance, satisfaction, and desire to recommend is associated with a lack of knowledge and participants' perceptions of the VIA examination conducted, both with digital images and without digital images.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The results in this study were similar to research conducted in Bogor, which showed that education level directly influenced perceptions of VIA examinations and other cervical cancer examinations. 21 This was also shown in previous studies which showed that the level of education related to the level of knowledge about cervical cancer, examinations in the framework of early detection of cervical cancer, the dangers posed, and examination methods. 12,21,22 Based on the analysis conducted, it is known that in general the poor level of acceptance, satisfaction, and desire to recommend is associated with a lack of knowledge and participants' perceptions of the VIA examination conducted, both with digital images and without digital images.…”
Section: Discussionsupporting
confidence: 62%
“…21 This was also shown in previous studies which showed that the level of education related to the level of knowledge about cervical cancer, examinations in the framework of early detection of cervical cancer, the dangers posed, and examination methods. 12,21,22 Based on the analysis conducted, it is known that in general the poor level of acceptance, satisfaction, and desire to recommend is associated with a lack of knowledge and participants' perceptions of the VIA examination conducted, both with digital images and without digital images. Therefore, one of the things that is considered the most important in carrying out VIA examinations is education and counselling.…”
Section: Discussionsupporting
confidence: 62%